Left sided acute appendicitis with intestinal malrotation in an adult, a diagnostic challenge - Gautam,, Rupesh; Adhikari, Deepak; De Lima, Gemma U.; Adhikari, Bhawana (Journal of Chitwan Medical College, 2018)
A 28-yr-old male presented with sudden onset pain at the epigastric region followed by left lower abdominal pain. CT scan of the abdomen revealed reverse relation of the superior mesenteric artery and superior mesenteric vein with large bowel loops including the cecum on left side and small bowel loops on the right. An inflamed appendix arising from the base of left sided cecum was identified. The intra operative findings were consistent with CT features. This is a rare case of left sided acute appendicitis with intestinal malrotation in an adult patient. CT scan is diagnostic modality of choice and excludes other possible disease presenting with similar clinical features.